INACCURACY OF BIPA LEARNER'S SPEECH BEGINNER LEVEL FROM KOREA: KETIDAKTEPATAN UJARAN PEMELAJAR BIPA TINGKAT PEMULA ASAL KOREA - Yohanna Nirmalasari (LLDIKTI Wilayah X, 2022)
BIPA learning includes learning reading, listening, writing, and speaking skills. All of these skills can represent the second language ability that has been acquired by a person. However, second language students often experience problems when learning a second language, for example when Korean students learn Indonesian as a second language. This can be observed from the inaccuracy of utterances found when speakers speak Indonesian. The inaccuracy of this utterance can be seen from two aspects, namely pronunciation and sentence structure. However, so far there has been no research on this even though research related to inaccuracies can be used as notes for BIPA teachers to classify words that must be exposed to students. Therefore, research related to speech imprecision needs to be done. The research method used is a case study qualitative research using oral speech data of Korean students during BIPA class and collected by tapping technique. The results of this study can be classified into two, namely the inaccuracy of speech in pronunciation and inaccuracy of speech in the structure of sentence functions. First, the inaccuracy of speech in pronunciation found is a change in consonant sounds, especially sound [k] and nasal sound [ŋ]. Second, the inaccuracy of speech in the sentence function structure category is (1) the inaccuracy of the structure of the function, namely the existence of a sentence structured S + O + P, (2) the inaccuracy of the arrangement of the types of words used to occupy the structure of the sentence function, namely the use of adverbs after the verb and the use of affixed verbs, and (3) the addition of personal and particle pronouns.